Assessment of Multidisciplinary Collaboration Among Healthcare Workers in Primary Health Care Center Nassarawa Jahun, Bauchi. - SALISU, Umar Muhammad UMAR; MUHAMMAD, Maryam Musa; MUHAMMAD Maimuna; Muhammad Fatima DAMBAM (RADINKA JAYA UTAMA PUBLISHER, PADANG, INDONESIA, 2026)
Effective multidisciplinary collaboration is a fundamental pillar of high-quality primary healthcare (PHC) services and a critical driver toward achieving Universal Health Coverage. This study evaluated the extent of multidisciplinary collaboration among healthcare practitioners at the Nasarawa Jahun Community Health Center in Bauchi, Nigeria. Utilizing a cross-sectional descriptive design, the study surveyed a total population of 57 healthcare workers, including nurses, community health practitioners, laboratory personnel, pharmacists, and other allied health professionals. Data were gathered via a structured questionnaire and analyzed using descriptive statistics. The findings revealed a high level of collaboration, underpinned by robust communication, shared decision-making, mutual respect, and clear role definition. Key facilitators of this effective teamwork include supportive leadership and a positive organizational culture. Respondents indicated that such collaboration significantly enhanced the quality of patient care, improved service efficiency, and increased overall job satisfaction. The study concluded that while multidisciplinary practices at the Nasarawa Jahun PHC are well-established, there is a continuous need to strengthen interprofessional education, maintain consistent leadership support, and implement regular team-building activities to sustain these high standards of integrated care.